UURI NO. 42 TAHUN 2009 â PERUBAHAN KETIGA UNDANG-UNDANG PAJAK PERTAMBAHAN NILAI - Sulistyani, Tri (PERMANA, 2010)
Value Added Tax (VAT) is one type of tax levied by the central government and used to finance the state household. In addition, VAT is also a kind of tax which is very close to the life of our communities everyday, because almost of any goods or services purchased by the public within the price of these goods contained VAT. Law of the Republic of Indonesia No. 42 Year 2009 is the third amendment of the Law on Value Added Tax and Sales Tax on Luxury Goods in one package, which in such Act, there are some very important changes that really needs to be known by the public. Act were issued on October 15, 2009, and takes effect April 1, 2010. But until now there are still many people who donât know about the changes that have a role in the new VAT law, which still must continue to be disseminated to the new VAT Act, so that people know about it. So if people see some things that have been stipulated in the Act in its implementation is not as it should, then the society may appeal to the parties that disadvantageous. Keywords: Value Added Tax